SCL LEAD to Improve quality of Student-Centered Learning Process in the Class of Discrete Mathematics - Adiwijaya, Adiwijaya; Palupi, Irma (Mosharafa: Jurnal Pendidikan Matematika, 2024)
Semakin banyak mahasiswa yang kurang tertarik pada beberapa mata kuliah di universitas, terutama matematika. Studi ini meneliti dampak pendekatan Student-Centered Learning (SCL) dalam pembelajaran Matematika Diskrit. Kami memperkenalkan metode SCL - Lecture’s Encouragement, Assistance, and Stimulating-Deliverance (SCL LEAD) untuk meningkatkan keterampilan belajar dengan mendorong interaksi dan kerja sama mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif melalui pre-test dan post-test untuk mengukur keterlibatan dan kinerja mahasiswa. Data dikumpulkan melalui observasi terstruktur, jaminan kesiapan, dan diskusi kelompok, kemudian dianalisis untuk menilai dampaknya terhadap keterampilan kognitif dan kolaboratif mahasiswa. Perbandingan antara ujian tengah dan akhir semester digunakan untuk mengukur efektivitas SCL LEAD, dengan statistik deskriptif dan inferensial untuk mengidentifikasi perubahan keterampilan dan pencapaian. Temuan menunjukkan bahwa SCL LEAD memotivasi mahasiswa untuk berpartisipasi aktif serta meningkatkan kompetensi dan kinerja dalam Matematika Diskrit, memberi wawasan berharga bagi pengembangan strategi pembelajaran berpusat pada mahasiswa di pendidikan matematika. The increasing disengagement of students in certain university courses, particularly in mathematics, is a growing concern. This study investigates the impact of the Student-Centered Learning (SCL) approach on the learning process for Discrete Mathematics. We introduce the Student-Centered Learning - Lecture’s Encouragement, Assistance, and Stimulating-Deliverance (SCL LEAD) method to enhance learning skills by fostering increased student interaction and cooperation. The study employs a quantitative approach, using pre-tests and post-tests to measure students’ engagement and performance. Data were gathered through structured observations, readiness assurance processes, and group discussions, all of which were documented and analyzed to assess their impact on students’ cognitive and collaborative skills. Comparative metrics between mid-term and final exams were used to determine the effectiveness of the SCL LEAD model, with descriptive and inferential statistics applied to identify changes in students' skills and achievements following the implementation of SCL LEAD. The findings suggest that SCL LEAD motivates active participation and enhances both competence and performance in Discrete Mathematics, offering valuable insights for advancing student-centered strategies in mathematics education.